Anti-inflammatory effects of Radix Aucklandiae herbal preparation ameliorate intestinal mucositis induced by 5-fluorouracil in mice. (10th May 2021) - Liu, Ju-Han; Hsieh, Chen-Hsi; Liu, Chia-Yuan; Chang, Ching-Wei; Chen, Yu-Jen; Tsai, Tung-Hu
Abstract: Ethnopharmacological relevance: 5-Fluorouracil (5-FU) is a chemotherapy agent that is widely used in clinical oncologic practice. However, intestinal mucositis is the most frequently occurring side effect of cancer therapy with 5-FU. Based on a literature survey, Radix Aucklandiae herbal preparation potentially ameliorates intestinal mucositis in 5-FU-treated mice. Aim of the study: The aim of this study was to investigate the inflammation and gastrointestinal regulation of intestinal mucositis induced by 5-FU, including the intestinal morphology, as well as the reduction in food intake, body weight loss, and diarrhea. Materials and methods: Intestinal mucositis was induced in mice by 5-FU (30 mg/kg, i.p., for 5 consecutive days). The dose-dependent Radix Aucklandiae herbal preparation (0.3, 1, and 3 g/kg/day, p.o.), loperamide (3 mg/kg/day, p.o.) or celecoxib (40 mg/kg/day, p.o.) was concurrently administered until the 7th day. Physical status observation, diarrhea assessment, serum proinflammatory cytokine levels, intestinal villus height and crypt depth, and total goblet cells from tissues were assessed. Results: The dosage regimen of 5-FU administration caused severe intestinal mucositis in mice, including damage to the intestinal morphology, accompanied by a reduction in food intake, body weight loss, and diarrhea. The high-dose Radix Aucklandiae herbal preparation significantly relieves 5-FU-induced intestinal mucositis by enhancing proliferative activity in epithelial crypts; improving anepithymia, body weight loss, and diarrhea; and displaying protective effects on goblet cells in intestinal mucosal epithelia. Activation of NF-κB in the intestinal mucositis model was also suppressed by the Radix Aucklandiae herbal preparation, suggesting that it is a potent inhibitor of NF-κB and proinflammatory cytokines, such as IL-1β, IL-6, TNF-α, and COX-2. Conclusions: Our data support the conclusion that the Radix Aucklandiae herbal preparation could effectively ameliorate 5-FU-induced gastrointestinal toxicity and be applied clinically for the prevention of intestinal mucositis during chemotherapy. Graphical abstract: Image 1